(untitled) (Research, Society and Development, 2022)
Objective: to find out, from the integrative review, what has been published about public health simulation scenarios in undergraduate health courses. Method: this is an integrative review carried out in Scielo.org, Lilacs and VHL published in the last 10 years, using the Bollean health descriptors: teaching AND simulation AND collective health OR Primary Health Care. Results: using the criteria of inclusion, 6 articles were found - most of the studies found were published in the field of nursing, consecutively in medicine and speech therapy. In short, they describe clinical simulation in collective health as an ability to develop actions in Primary Health Care and analysis of students’ knowledge, satisfaction and confidence based on the use of this method in higher education. Final considerations: with this study, it was possible to know what has been published about simulation in the training field of primary care for future health professionals at university level. Few studies were found in this review, which allows us to problematize the need for future studies, given the effectiveness of the simulation method for teaching-learning.